Hepatic-stellate-cell-targeted delivery of PU.1 decoy ODN by Apt-Tan attenuates liver fibrosis in mice - Yong Tan; Li-Ye Zhang; Yue Sun; Xiao-Jie Luo; Si-Yuan Wu; Xian-Zhi Wu; Yan-Qiong Zhang; Ying Wang; Bo-Tao Li; Yi-Ran Ni; Lan Ma; Jiang-Feng Wu (Molecular Therapy: Nucleic Acids)
Targeted therapeutics for liver fibrosis (LF) are unavailable. PU.1 is a pioneer transcription factor (TF) that promotes hepatic stellate cell (HSC) activation and LF. PU.1 decoy oligodeoxynucleotides (ODNs) can potentially repress LF by capturing PU.1. In this study, we used Apt-Tan, a hepatic stellate cell (HSC)-internalizing DNA aptamer selected through the cell systematic evolution of ligands by exponential enrichment (Cell-SELEX), and validated the anti-LF effect of a combination of Apt-Tan and PU.1 decoy ODN in mice. Furthermore, intravenous injection of Apt-Tan- PU.1 decoy ODN repressed the expression of PU.1 downstream pro-fibrotic genes such as TIMP1, alleviated liver injury, and reduced extracellular matrix deposition in mice model of LF induced by CCL4. Apt-Tan- PU.1 decoy ODN demonstrated anti-fibrosis potential and warranted further investigation.